Hunting and trading bushmeat in the Kilombero Valley, Tanzania: motivations, cost-benefit ratios and meat prices. (1st July 2014) - NIELSEN, MARTIN REINHARDT; MEILBY, HENRIK
SUMMARY: Bushmeat hunting in the savannah biomes of East Africa is often considered to be subsistence oriented and undertaken as a gap-filler in the lean agricultural season. The price of bushmeat is furthermore often thought uniform regardless of species, but if hunting is commercially oriented and price premiums are paid for particular species this needs to be considered. This paper investigates these issues in the Kilombero Valley of Tanzania, based on one year of market data and interviews with 80 hunters, 169 traders and 67 retailers. Motivations were overwhelmingly commercial and the bushmeat trade constituted a year-round income generating activity. Monte Carlo simulations based on the deterrence model revealed average cost-benefit ratios of 0.15–0.43 for hunters, 0.56–0.62 for traders and 0.88 for retailers, and a 12–401 fold increase in likelihood of apprehension may be required to render the trade unprofitable. Willingness-to-pay data showed that elephant, buffalo, hippopotamus, puku, bushpig and warthog meat were preferred. Enhanced enforcement may thus drive prices for these species higher, encouraging hunters to seek ways around constraints. Community-based wildlife management and improved firearms control may be the most pragmatic ways to regulate the trade.